2011
DOI: 10.1603/me11043
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Efficient Transovarial Transmission of Culex Flavivirus byCulex pipiens(Diptera: Culicidae)

Abstract: This study determined the transovarial transmission (TOT) potential and tissue tropisms of Culex flavivirus (CxFV), an insect-specific flavivirus, in Culex pipiens (L.). Several hundred mosquito egg rafts were collected in the field, transferred to the insectaries, reared to the fourth larval instar, and identified using morphological characteristics. Cx. pipiens were reared to adults, allowed to oviposit in individual containers, and tested for CxFV RNA by reverse transcription-polymerase chain reaction (RT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 42 publications
6
111
0
1
Order By: Relevance
“…Studies of the tissue tropisms of CxFV, 35 another insect-specific flavivirus, in naturally infected Culex pipiens mosquitoes revealed a pervasive infection, with viral RNA detected in all tissues tested (salivary glands, ovaries, testes, head, fat body, and midgut). 18 Culex flavivirus RNA was also detected in all life stages (eggs, larvae, pupae, and adults from a naturally infected laboratory colony), with viral titers estimated to be as high as 8.95 log 10 RNA copies per individual. 20 Interestingly, one study 22 reported that saliva collected from Culex quinquefasciatus mosquitoes co-inoculated with CxFV (Izabal strain) and WNV contained both viruses, but no CxFV was detected in the saliva from singly infected mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the tissue tropisms of CxFV, 35 another insect-specific flavivirus, in naturally infected Culex pipiens mosquitoes revealed a pervasive infection, with viral RNA detected in all tissues tested (salivary glands, ovaries, testes, head, fat body, and midgut). 18 Culex flavivirus RNA was also detected in all life stages (eggs, larvae, pupae, and adults from a naturally infected laboratory colony), with viral titers estimated to be as high as 8.95 log 10 RNA copies per individual. 20 Interestingly, one study 22 reported that saliva collected from Culex quinquefasciatus mosquitoes co-inoculated with CxFV (Izabal strain) and WNV contained both viruses, but no CxFV was detected in the saliva from singly infected mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…It is now apparent that these viruses are widespread in nature and that many are probably maintained by vertical transmission. [16][17][18][19] Some studies also suggest that superinfection exclusion (cells infected with one virus are refractory to infection by a second related virus) may occur between some insectspecific viruses and pathogenic arboviruses, 20,21 altering the vector competence of the mosquito host. In vivo and in vitro studies investigating interactions between two insect-specific flaviviruses (Culex flavivirus [CxFV] 20, 22 and Palm Creek virus [PCV] 21 ) with West Nile virus (WNV), have shown modulation of WNV replication and dissemination in dually infected mosquitoes, suggesting that some insect-specific viruses may alter the mosquito's ability to serve as a competent vector for certain pathogenic arboviruses.…”
Section: Introductionmentioning
confidence: 99%
“…CxFV was detected using reverse transcription-polymerase chain reaction 2012-2013 Indonesia, Singapore, Australia, Tahiti, Germany [ 16 , 20 -24 ] (RT-PCR) in Culex pipiens (L) mosquitos captured in the fi eld. Their progeny were viral infected as well and viral RNA was detected in several progeny tissues (salivary glands, ovaries, testes, head, fat bodies, and midgut) [ 27 ]. Previously, TOT had been proposed as a mechanism contributing to the spread of Zika and yellow fever viruses in Uganda [ 28 ].…”
Section: Mosquitoesmentioning
confidence: 99%
“…In addition to flaviviruses pathogenic to vertebrates, a number of insect-specific flaviviruses (ISFs) have been described from mosquitoes that do not replicate in vertebrate cells but specifically in insect hosts (Blitvich & Firth, 2015). These are believed to be vertically transmitted as they are not infectious by oral feeding (Bolling et al, 2012;Cook et al, 2012;Lutomiah et al, 2007;Saiyasombat et al, 2011). Interestingly, a number of them have been shown to negatively affect replication of medically important flaviviruses in co-infected or superinfected mosquitoes (Bolling et al, 2012;Goenaga et al, 2014;Hall-Mendelin et al, 2016;Hobson-Peters et al, 2013;Kenney et al, 2014).…”
mentioning
confidence: 99%